Degradable Bioplastic Developed from Pine-Wood Nanocellulose as a Filler Combined with Orange Peel Extract - Alyaa Farrah Dibha; Masruri Masruri; Arie Srihardyastutie (Universitas Gadjah Mada, 2023)
This research presents the degradable bioplastics developed from pinewood nanocellulose as a filler in PVA matrices. The steps involve the isolation and characterization of cellulose and nanocellulose. Meanwhile, the manufacturing of degradable bioplastic involves the combination of PVA, nanocellulose, and with or without orange peel extract. The effect of bioplastics without the addition of citric acid and orange peel extract is also reported as a comparison. It is found that orange peel extract improves the tensile strength (1708.54 kPa), elastic modulus (42.71 kPa), elongation (40%), and degradability (78.44% in 2 weeks) compared to bioplastic without the orange peel extract. These results indicate that orange peel extract acts as a reinforcing agent in PVA-nanocellulose bioplastic.